PENGARUH PERENCANAAN TERHADAP KINERJA KARYAWAN BAGIAN DIVISI KELAPA SAWIT PADA KANTOR PTP MITRA OGAN KANTOR PIN 1 PENINJAUAN OGAN KOMERING ULU - Yansahrita, Yansahrita; Sari, Sri Sarwo; Kasisariah, Tri Rusilawati; Darmanah, Darmanah; Dika, Aflah (STMIK Pringsewu, 2024)
Supporting the progress and development of an organization really needs to be done seriously and continuously in all fields and all aspects of life. The availability of quality human resources and a high work ethic is the main capital for an organization to be on par with other organizations. The problem faced is how does planning affect the performance of employees of the Palm Oil Division at the PTP Mitra Ogan Office Pin 1 Review Office Ogan Komering Ulu. The purpose of this research is to determine the effect of planning on the performance of employees in the Palm Oil Division at the PTP Mitra Ogan Office Pin 1 Review Ogan Komering Ulu Office and to be useful as reference material for further research regarding employee planning and performance. The hypothesis proposed is that planning has a positive effect on the performance of employees of the Palm Oil Division at the PTP Mitra Ogan Office, Pin 1 Review Office, Ogan Komering Ulu. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, it was found that there was a correlation between planning in an effort to improve the performance of employees in the Palm Oil Division at the PTP Mitra Ogan Office, Pin 1 Office for the Ogan Komering Ulu Review, an r figure of 0.57 was obtained. After consulting with conservative standards, it is between 0.400- 0.599 which is included in the moderate correlation. So it can be said that there is a moderate influence between planning on the performance of employees of the Palm Oil Division at the PTP Mitra Ogan Office Pin 1 Review Office Ogan Komering Ulu.